2016
DOI: 10.1515/bj-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin and Podocalyxin - New Podocyte Proteins for Early Detection of Secondary Nephropathies

Abstract: In the last two decades a great progress was observed in understanding of podocytes, their specific structure and function identifying many specific podocyte proteins, such as nephrin and podocalyxin. Podocytes form the final barrier to plasma proteins leakage. Nephrin as a main component of the filtration diaphragm forms a physical barrier while podocalyxin as sialoglycoprotein forms an electrostatic barrier. Podocyte damage, i.e. podocytopathies and their loss through urine-podocyturia, are crucial in pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…In our study both nephrin and podocalyxin levels were associated with severe tubular atrophy, interstitial fibrosis and interstitial inflammation. There are several studies affirming this correlation as well as the fact that NEP levels are correlated also with albuminuria while changes in NEP excretion have been linked to podocyte injury [19]- [21]. In our study, we also reported that segmental glomerulosclerosis was significantly associated with NEP/CR ratio.…”
Section: Discussionsupporting
confidence: 83%
“…In our study both nephrin and podocalyxin levels were associated with severe tubular atrophy, interstitial fibrosis and interstitial inflammation. There are several studies affirming this correlation as well as the fact that NEP levels are correlated also with albuminuria while changes in NEP excretion have been linked to podocyte injury [19]- [21]. In our study, we also reported that segmental glomerulosclerosis was significantly associated with NEP/CR ratio.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, IF treatment also led to structural damage to the filtration barrier, which is proved by the increased presence of another protein -NPH -in the urine of IF-treated animals. Nephrin is a structural protein of gap junctions in the foot processes of podocytes [35,36]. These visceral epithelial cells are highlyspecialized units lining the outer surface of the glomerular capillaries and that neighbor cells of the Bowman's capsule [37].…”
Section: Discussionmentioning
confidence: 99%
“…As far as the PDC/CR urine level is concerned, our study interestingly validated the correlation with activity parameters, such as severe interstitial inflammation. To the best of our knowledge, few studies have assessed both markers (PDC/CR and NEP/CR ratio) simultaneously in patients with GN [ 10 , 19 , 20 ]. A previous study assessed the impact of systemic lupus erythematosus (SLE) on urinary levels of podocalyxin, as well as its correlation with renal biopsy histological parameters, proteinuria, and disease activity [ 20 ].…”
Section: Discussionmentioning
confidence: 99%